Treatment of Dairy Industry Wastewater and Crop Irrigation Water Using AgBr-Coupled Photocatalysts - M. Hernández-Laverde; J. J. Murcia; J. A. Navío; M. C. Hidalgo; F. Puga (Nanomaterials)
This work describes the application of three different AgBr heterojunctions with TiO2, SnO2 and WO3 in the treatment of two water sources: wastewater from a dairy industry facility (WDI) and water from a polluted river (WPR). All heterojunctions were widely characterised, and it was observed that the physicochemical properties of all the coupled materials were similar; however, the highest elimination of Enterobacteriaceae (>90%) was obtained with the AgBr/WO3(20%) photocatalyst in WDI. Under the same conditions, with this photocatalyst, the complete removal of bacteria (i.e., E. coli, total coliforms and other Enterobacteriaceae) was achieved in WPR. The chlorides, hardness and colour in the two water samples decreased after photocatalytic treatment with all the coupled materials. However, nitrate levels and chemical oxygen demand increased due to the possible formation of intermediary species from the photodegradation of organic pollutants and the release of metabolic intermediates from bacterial degradation during the photocatalytic process. Overall, heterogeneous photocatalysis based on AgBr-coupled materials shows potential as a tertiary treatment for WDI and for the purification of vegetable irrigation water. However, it is still important to consider the need to optimise the integrity of photocatalytic materials in order to maintain their bactericidal effectiveness through continuous reuse.